Corporate governance mechanisms and bank performance: evidence from the Greek banks during crisis period - Andreas G. Georgantopoulos; Ioannis Filos (Investment Management & Financial Innovations, 2017)
This paper is the first research attempt that investigates the impact of a large number of corporate governance mechanisms on the performance of Greek banks,employing widely accepted in the literature of corporate governance econometric models. Results indicate that system GMM models are more suitable methodological tools than pooledOLS and fixed effects models to address well-known econometric problems, such as endogeneity, simultaneity and unobserved heterogeneity of individual banks. The findings, as derived from the application of GMM models, imply that increasing the board size and the number of independent directors can both have positive impact on the performance of Greek banks, but only up to a certain point. Thus, bank efficiency will increase as board size and the proportion of independent directors grow up to a point where these relationships hit a maximum from which bank performance decreases. Our multi-model estimations failed to trace any significant contribution of the number of female and foreign directors on the performance of Greek banks. Finally, the dual appointment of a CEO as Chairman appears to affect negatively two out of four proxies of bank performance. Overall, the results provide support for the positive impact of corporate governance mechanisms on the performance of Greek banks. The significance of these findings increases, considering that the period under study (2008-2014) is marked by high market volatility and uncertainty due to the well-known debt crisis that plagues Greece since the beginning of 2008.